Synthesis of alkali activated materials incorporating municipal solid waste incineration bottom ash - Zhu, Weiping (Nanyang Technological University, 2018)
Incineration bottom ash (IBA) is the ash residue after incineration of municipal solid waste. Instead of disposing of IBA in landfills or involving costly pre-treatments, this study explores the utilization of un-treated IBA as precursor and/or gas-forming agent to synthesize (lightweight) alkali-activated materials (AAMs) for civil engineering applications. Chemical structures and compositions of the resulting alkali-activated IBA (AA-IBA) binder were analysed by means of selective chemical extractions, X-ray powder diffraction (XRD), thermal gravimetric analysis (TGA), solid state nuclear magnetic resonance (NMR) spectroscopy with magic angle spinning (MAS) and Fourier-transform infrared (FTIR) spectroscopy. It was found that the AA-IBA binder mainly consists of calcium silicate hydrates and geopolymer gel. To enhance the utilization potential, IBA was classified into categories according to sizes and types (i.e. glass IBA, ferrous IBA and nonferrous IBA) for strategic utilizations. The glass IBA, rich in amorphous silica, is a suitable AAM precursor. Resulting alkali-activated glass IBA (AA-glass IBA) show compressive strength up to 70 MPa, sufficient for structural applications. The nonferrous IBA, containing more metallic aluminum, was used as gas-forming agent to aerate the AA-glass IBA. This strategic use of classified IBA resulted in lightweight aerated materials with higher strength-to-density ratio, and greater IBA utilization rate as compared to un-classified AA-IBA.